Gridded cartograms as a method for visualising earthquake risk at the global scale - Hennig, B (Taylor and Francis, 2013)
The assessment of natural events that can turn into disasters where people live is usually accompanied by maps visualising the specific topic in its spatial setting and putting the physical environment into the main focus. Such conventional mapping approaches, however, can often fail to give an intuitive understanding of the underlying quantitative dimension of the associated risk to people and a fuller appreciation of the interrelation between humans and their natural environment. The method presented here demonstrates an alternative way of mapping environmental risk. A gridded cartogram approach is introduced and illustrated with examples drawn from data documenting globally significant earthquakes that have occurred since 2150 BC. Gridded cartograms are a new map projection. They are created by starting with an equally distributed grid onto which a density-equalising cartogram technique is applied. Each individual grid cell is resized according to specific quantitative information. The underlying grid ensures the preservation of an accurate geographic reference to the real world. It allows gridded cartograms to be used as basemaps, new projections, onto which other information can be mapped. Earthquake intensity on a gridded population cartogram highlights those zones where most people live in these risk environments and minimises information about where earthquakes still occur, but where they matter less for human populations. Gridded cartograms also allow any other quantitative data to be used in the actual transformation. This is demonstrated with gridded cartograms from earthquake intensity data, resulting in very unusual depictions and new perspectives of the surface of the planet.